Overview of knowledge mangement in organizations - Huang, Yu. (My University, 2008)
This paper looked into the knowledge management from the organizational perspective. Author introduced definition of knowledge management, explicit knowledge and tacit knowledge, and three attributes of effective knowledge management?maturity, dynamic and self-growth. Subsequently, the author explained organizational culture and structure which can best support successful knowledge management by reviewing literatures and illustrating a knowledge enterprise model. To manage knowledge effectively, the organization should create a knowledge-sharing culture whose component is trust and consider it from four targets?interpersonal, group, organizational and institutional. Trust should go through the process of knowledge management, and emphasize trust to people and to knowledge content simultaneously. Organizational structure should facilitate knowledge sharing and be able to manage tacit knowledge. Also, it should align with organization strategies, fit the culture and lead to organization learning by using technology as an enabler.
Keywords: Knowledge management